Genomic Analysis of Klebsiella pneumoniae ST258 Strain Coproducing KPC-2 and CTX-M-14 Isolated from Poultry in the Brazilian Amazon Region - Tiago Barcelos Valiatti; Rodrigo Cayô; Fernanda Fernandes Santos; Francisco Ozório Bessa-Neto; Ramon Giovani Brandão Silva; Ruanita Veiga; Márcia de Nazaré Miranda Bahia; Lívia Maria Guimarães Dutra Guerra; Antônio Carlos Campos Pignatari; Cintya de Oliveira Souza; Danielle Murici Brasiliense; Ana Cristina Gales (MDPI AG, 2022)
This study aimed to characterize a Klebsiella pneumoniae strain (KP411) recovered from the stool samples of poultry (Gallus gallus) in the Brazilian Amazon Region. The whole-genome sequencing of KP411 revealed the presence of an important arsenal of antimicrobial resistance genes to β-lactams (blaCTX-M-14, blaTEM-1B, blaKPC-2, blaSVH-11), aminoglycosides [aph(3")- Ib, aph(6)-Id, aph(3')-Ia], sulfonamides (sul1, sul2), quinolones (oqxAB), fosfomycin (fosAKP), and macrolides [mph(A)]. Furthermore, our analyses revealed that the KP411 strain belongs to the ST258 clonal lineage, which is one of the main epidemic clones responsible for the dissemination of KPC-2 worldwide. Our data suggest that food-producing animals may act as reservoirs of multidrug-resistant K. pneumoniae belonging to the ST258 clone, and, consequently, contribute to their dissemination to humans and the environment.